Free Nutritious Meals Policy as a Stimulus for Strengthening the Economic of Farmers and Traditional Markets: A Literatur Review - Setiabudi, Tardi; Rahmawati, Rahmawati; Supriantino, Tino (Future Science, 2025)
This study examines the Free Nutritious Meals (MBG) policy as a tool for strengthening the local economy, with a focus on farmers and traditional markets as key actors in the food supply chain. The primary issue of this study is the lack of integration between nutrition policies and regional economic development. The purpose of this study is to analyze how MBG can function as a stimulus for the local economy through a literature review approach. Data were obtained from academic literature, reputable journals, and recent policy reports, then analyzed using content analysis techniques based on food security theory, local economic development, and Edward III's policy implementation model. The results show that MBG has the potential to be a productive policy that strengthens food security, increases farmers' income, and revitalizes traditional markets as drivers of the people's economy